Reserve Stocks as External Targets and the Stability of Alternative Exchange Rate Systems - Levin, Jay H. (Review of Economic Studies, 1977)
Journal Article Reserve Stocks as External Targets and the Stability of Alternative Exchange Rate Systems Get access Jay H. Levin Jay H. Levin Wayne State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 59–69, https://doi.org/10.2307/2296973 Published: 01 February 1977 Article history Received: 01 November 1975 Accepted: 01 August 1976 Published: 01 February 1977